Genetic diversity and heterotic orientation of South Africa maize inbred lines towards tropical and temperate testers - Shandu, S.F.; Derera, J.; Mashingaidze, Kingstone; Gasura, E. (Springer, 2021)
An ecient hybrid breeding program denes and utilizes few heterotic groups. The objectives of this study were to determine genetic diversity and alignment of South Africa maize inbred lines collection towards tropical and temperate testers. Forty-two maize inbred lines were genotyped with 56110 single nucleotide polymorphism (SNP) DNA markers, using the Illumina MaizeSNP50 Bead chip. The 42 lines were crossed to two tropical and two temperate inbred line testers. The testcrosses were evaluated across seven environments, in South Africa, during 2014-2016. Genotypes and specic combining ability (SCA) effects of hybrids were signicantly different (P<0.05) for grain yield. There was a weak correlation between molecular genetic distances and both grain yield mean and specic combining ability effects of hybrids, indicating that productivity of maize inbred lines could not be reliably determined based on molecular genetic distances. The SCA data was capable of classifying these maize inbred lines into three heterotic groups with respect to both tropical and temperate testers. Only a few lines could not be grouped on the basis of SCA data. The study also indicated high level of diversity among the maize inbred lines, which was shown by both the dendogram and molecular genetic distances. The SNP marker data classied the inbred lines into 11 clusters that could be simplied into three major groups of normal maize endosperm and two groups of quality protein maize (QPM) endosperm types. However, the SNP data indicated that maize lines were more aligned towards tropical than temperate inbred testers. This information would be useful for simplifying heterotic classication of the lines with profound implications for breeding progress.